Institutional Design, Macroeconomic Policy Coordination and Implications for the Financial Sector in the UK - Muhammad Ali Nasir; Milton Yagob; Alaa Solimanc; Junjie Wud (Journal of Central Banking Theory and Practice, 2017)
This study has analysed the implications of institutional design of macroeconomic policy making institutions for the macroeconomic policy interaction and financial sector in the United Kingdom. Employing a Vector Error Correction (VEC) model and using monthly data from January 1985 to August 2008 we found that the changes in institutional arrangement and design of policy making authorities appeared to be a major contributing factor in dynamics of association between policy coordination/combination and financial sector. It was also found that the independence of the Bank of England (BoE) and withdrawal from the Exchange Rate Mechanism led to the increase in macroeconomic policy maker's ability to coordinate and restore financial stability. The results imply that although institutional autonomy in the form of instrument independence (monetary policy decisions) could bring financial stability, there is a strong necessity for coordination, even in Post-MPC (Monetary Policy Committee) and the BoE independence.
Keywords: E52; E58; E44; 330; Macroeconomic Policy Interaction; Institutional Design; Financial Markets; Policy Coordination; Central Bank Independence.